Rumen ciliates in the African (Cape) buffalo (Syncerus caffer caffer) living in the vicinity of the Orpen Gate entrance into Kruger National Park, South Africa - Booyse, Dirk G.; Dehority, Burk A.; Reininghaus, Björn (Zootaxa, 2014)
Samples of rumen contents were obtained from 10 African (Cape) buffalo living in the vicinity of the Orpen Gate entrance into Kruger National Park in South Africa. Total number of ciliate protozoa per animal ranged from 3.15 to 23.25 x 103. Forty three different species and forms were observed, of which 35 are a new host record. The total number of species and forms per animal varied from 10 to 17. Eudiplodinium maggii occurred in all 10 animals, followed by Dasytricha ruminantium in nine animals. Diplodinium posterovesiculatum, Eudiplodinium magnodentatum and Ostracodinium mammosum were present in seven animals with all other species and forms occurring in five or less animals.